Pengaruh Harga, Promosi Dan Kualitas Produk Terhadap Minat Beli Pengguna E-Commerce TikTok Shop Pada Mahasiswa Sekolah Tinggi Ilmu Ekonomi Bentara Persada Di Kota Batam - Elizabert , Yesita; Junianto , Pilifus; Dabur , Feliks (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2025)
ABSTRACT This study aims to determine the Influence of Price, Promotion, and Product Quality on the Buying Interest of Tiktok Shop E-Commerce Users in Students at the Bentara Persada College of Economics in Batam City. This study uses a quantitative method. The sample in this study amounted to 65 respondents. Data processing in this study uses SmartPLS software version 4.1.1.2. The results of data processing on price variables found that tstatistics were 3.765 > 1.969 and Pvalues value was 0.000 < 0.05, so the price had a positive and significant effect on buying interest. The promotion variable found that tstatistics were 2.594 > 1.969 and Pvalues value was 0.010 < 0.05, so promotion had a positive and significant effect on buying interest. The product quality variable found that the tstatistics were 0.309 < 1.969 and the Pvalues were 0.757 > 0.05, so the product quality did not have a positive and significant effect on buying interest. From the R2 test, it was found that price, promotion and product quality contributed 32.5% to buying interest, while the remaining 67.5% of the buying interest variable was influenced by other independent variables that were not described in this study. Year 2025